2016
DOI: 10.11002/kjfp.2016.23.5.696
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the re-extraction process of ethanol from catechin components from Korean green tea extract

Abstract: The purpose of this study was to determine the optimum re-extraction conditions of ethanol from catechin in Korean green tea (Camellia sinensis L.) using response surface methodology (RSM). The experiments were carried out according to a five level and two variable central composite design (CCD). The two independent variables were solvent ratio to sample content (1, 4, 7, 10, 13 mL/g) and extraction temperature (-20, -10, 0, 10, 20℃) on the dependent variables including yield, epigallocatechin (EGC), epicathch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Glutamic acid and glycine were identifed as the two major amino acids in both APT6 and APT6 < 3 kDa, with concentrations ranging from 12.57 to 13.23 g/100 g and 9.94 to 11.18 g/100 g, respectively. Tis fnding is consistent with previous studies that have reported glutamic acid and glycine as the predominant amino acids in other BGEs [14,17]. Aspartic acid, proline, alanine, leucine, lysine, and arginine were also abundant in APT6 and APT6 < 3 kDa.…”
Section: Amino Acid Composition Of Apt6 and Apt6 < 3 Kdasupporting
confidence: 92%
See 1 more Smart Citation
“…Glutamic acid and glycine were identifed as the two major amino acids in both APT6 and APT6 < 3 kDa, with concentrations ranging from 12.57 to 13.23 g/100 g and 9.94 to 11.18 g/100 g, respectively. Tis fnding is consistent with previous studies that have reported glutamic acid and glycine as the predominant amino acids in other BGEs [14,17]. Aspartic acid, proline, alanine, leucine, lysine, and arginine were also abundant in APT6 and APT6 < 3 kDa.…”
Section: Amino Acid Composition Of Apt6 and Apt6 < 3 Kdasupporting
confidence: 92%
“…Following ultrafltration with a 3 kDa cutof, threonine, leucine, tyrosine, and phenylalanine were increased, whereas aspartic acid, glycine, and cysteine were decreased. Te essential amino acid (EAA) content of APT6 and APT6 < 3 kDa was found to be 32.96% and 35%, respectively, which surpassed the EAA content of black goat meat extract (23.9%) [17] and veal meat and bone hydrolysate (21.82%) [18]. However, the reported EAA content of chicken meat hydrolysate (44.5%) [19] exceeds that of APT6 and APT6 < 3 kDa.…”
Section: Amino Acid Composition Of Apt6 and Apt6 < 3 Kdamentioning
confidence: 85%